Development and Content Validity of ‘Ayo Jajan Sehat’ Poster as a Nutrition Education Media for Elementary School Children - Haryanti, Niken Diah; Rahmawaty, Setyaningrum (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The objective of this study is to conceptualize and evaluate the effectiveness of nutrition education media specifically tailored for elementary school stu-dents, presented in the form of posters promoting healthy snack choices. Methodology: This research method uses the Research and Development (R&D) method of Analysis, Design, Development (ADD) which is then tested for validity us-ing the CVI formula. This validity test involved 6 experts who consisted of 2 nutrition experts, 2 language experts, and 2 media experts. Results: Based on the results of the expert judgment, the CVI value of the nutrition expert of 0.96 is included in the very suitable category, the language expert of 0.96 is included in the very suitable category and the media expert of 0.86 is included in the very suitable category. So, it can be concluded that the ed-ucational media poster “Ayo Jajan Sehat” is suitable for nutrition education for elementary school students. Applications/Originality/Value: This study contributes to the development of effective visual-based nutrition education tools tailored for young learners. The "Ayo Jajan Sehat" poster serves as a practical and validated medium to enhance students' awareness of healthy snack choices. It can be integrated into school health programs and classroom learning to support early intervention in building healthy eating habits, thus promoting long-term wellness from an early age.